(untitled) (Global Journal of Management and Business Research, 2020)
The study examines the empirical relationship between exchange rate, interest rate and inflation in the context of Sub -Sahara African countries using panel data over 1980-2012 periods. The estimated values of the pooled, fixed and random effects models reveal identical results that interest rate and inflation maintain a monotonous relationship with the exchange rate, though the relationship is insignificant for interest rote only in the random effect model based on 1% level of significance. However; the result of the Hausman Test shows that the random effect model is not appropriate rather, the fixed-effect model is preferred. Based, on the Johansen Fisher panel co integration approach, a long-run relationship is established among the specified variables. Finally, it was discovered that the interest rate is weakly exogenously determined in the selected-countries throughout the freely and managed floating exchange rate systems.